High‐dose vasoactive agents in aeromedical retrievals for septic shock: A role for vasopressin?. (13th December 2022) - Aston, Ben; Allen, Katherine; Hamilton, Alistair
Abstract: Objective: To determine the number of patients retrieved by aeromedical teams for septic shock requiring vasopressor support who meet criteria for vasopressin therapy under the Surviving Sepsis Campaign 2021 guidelines. Methods: Retrospective chart review of patients transferred by LifeFlight Retrieval Medicine on vasopressors over 2 years. Results: One thousand one hundred and fifty‐eight patients were retrieved on vasopressor therapy, with 428 requiring infusions for septic shock. One hundred and fifteen of these met criteria for administration of vasopressin under Surviving Sepsis Campaign guidelines. Conclusion: A sufficient percentage of patients on vasopressors for septic shock require vasopressin therapy to meet current best treatment guidelines, and the inclusion of vasopressin in retrieval drug kits should be considered by Australian aeromedical services. Abstract : Retrospective chart review of aeromedical retrievals of patients with septic shock to determine how many patients met criteria for vasopressin under the Surviving Sepsis Campaign 2021 guidelines. 1, 158 patients were retrieved on vasopressor therapy, with 428 requiring infusions for septic shock. 115 of these met criteria for administration of vasopressin under Surviving Sepsis Campaign guidelines.